Agroforestry Model in Leimea Sorin Village, Emerera District, Timor Leste - SOARES, Cristina (PT Keberlanjutan Strategis Indonesia, 2024)
Agroforestry is an optimal and sustainable management of land use, by combining forestry and agricultural activities on the same land management unit by taking into account physical, social and economic environmental conditions. The purpose of this study is to calculate the value of farmers' income from the results of the agroforestry model, and the best feasibility analysis on consideration of three factors, namely economic, social and ecological. This research was carried out in the village of Leimea Sorin, Ermera District, Timor Leste in March-May 2021 using qualitative and quantitative methods. The data used in this study are data obtained directly from agroforestry farmers in the Ermera district of Timor Leste by means of interviews with the help of a questionnaire. Economic data analysis using three criteria NPV, BCR and IRR, and social and ecological analysis using qualitative descriptive. The results of the financial analysis show that the NPV is 220,184.66, the BCR is 28.7 and the IRR is 35%. The results of the social analysis show that the social aspect in the application of agroforestry in the village of Leimea Sorin Balu is the local community of the Kemak ethnic group of agricultural crops as their daily livelihood such as vanilla, coffee, teak, and others. And the ecological aspect is the results of the study show that the agroforestry model in the village of Leimea Sorin is an agroforestry system that has polycultural properties, and provides various benefits for the community compared to non-agroforestry systems.